The impact of blade technology on Paralympic sprint performance between 1996 and 2016: bilateral amputees` competitive advantage - Tuakli-Wosornu, Y. A.; Li, X.; Ona Ayala, K. E.; Wu, Y.; Amick, M.; Frumberg, D. B. (Adapted Physical Activity Quarterly, 2023)
It is known that high-performance sprinters with unilateral and bilateral prosthetic lower limbs run at different speeds using different spatiotemporal strategies. Historically, these athletes still competed together in the same races, but 2018 classification rule revisions saw the separation of these two groups. This study sought to compare Paralympic sprint performance between all-comer (i.e., transfemoral and transtibial) unilateral and bilateral amputee sprinters using a large athlete sample. A retrospective analysis of race speed among Paralympic sprinters between 1996 and 2016 was conducted. In total, 584 published race results from 161 sprinters revealed that unilateral and bilateral lower-extremity amputee sprinters had significantly different race speeds in all three race finals (100 m, p value <.001; 200 m, <.001; 400 m, <.001). All-comer bilateral amputee runners ran faster than their unilateral counterparts; performance differences increased with race distance. These data support current classification criteria in amputee sprinting, which may create more equal competitive fields in the future.